What policies do populists pursue when in power? Results of selected studies - Luisa Dörr; Niklas Potrafke; Felix Rösel; Tuuli Tähtinen (EconPol Forum, 2024)
Populist-led countries tend to experience lower economic growth and less integration into the global economy compared to countries not governed by populists. Recent studies at the municipal level provide convincing evidence of the impact of populists in office. During their tenure, populist mayors have restricted immigration and social polarization has increased. The election of populist mayors with anti-immigration agendas also influences attitudes toward foreign migrants, leading to a higher probability of hate crimes against immigrants. Populist representation in municipal councils can lead to shifts in the ideological positions of other parties.
Keywords: 330